Cholecystectomy in 23 cats (2005‐2021). Issue 1 (20th October 2021) - Simpson, Matthew; Neville‐Towle, Jack; Lee, Karla; Rossanese, Matteo
Abstract: Objective: To describe the clinical presentation, treatments, and long‐term outcomes following cholecystectomy in cats. Study design: Clinical retrospective study. Animals: Twenty‐three client‐owned cats. Methods: Medical records of all cats undergoing cholecystectomy between 2005 and 2021 at a single referral hospital were retrospectively reviewed. No cats were excluded. An owner questionnaire assessed long‐term outcomes. Results: Vomiting, jaundice, and abdominal pain were the most common clinical signs; median duration of signs was 4 days (range 1‐21). Cholelithiasis was the major indication for cholecystectomy followed by cholecystitis. Intraoperative hypotension and postoperative anemia were commonly encountered. Nine cats required a postoperative blood product transfusion. Cardiopulmonary arrest and death occurred in five cats. Eighteen cats (78.3%) survived to discharge. Long‐term follow up (>60 days) was available for 16 cats at a median of 1003 days (range 81‐4995). Fifteen cats survived over 6 months with eight cats (44.4%) surviving over 3 years. The most common short‐term and long‐term postoperative complication was vomiting. Owners assessed postoperative outcome as excellent in all cats and quality of life as excellent or good. Conclusion: The most common indication for cholecystectomy was cholelithiasis. Perioperative complications were commonly encountered. Perioperative mortality rate was 21.7%. Long‐term owner evaluation of clinical outcome was considered excellent. Clinical significance: Cats undergoing cholecystectomy for non‐neoplastic causes can have a favorable prognosis for recovery and quality of life. Concurrent extrahepatic biliary duct obstruction is not a contraindication for cholecystectomy provided that patency of the common bile duct is restored.